Randomized, Double-Blinded Trial of Magnesium Sulfate Tocolysis versus Intravenous Normal Saline for Preterm Nonsevere Placental Abruption - Colón, Iris; Berletti, Monica; Garabedian, Matthew J.; Wilcox, Nicole; Williams, Kristin; El-Sayed, Yasser Y.; Chueh, Jane (American Journal of Perinatology, 2016)
Objective To evaluate the efficacy and safety of magnesium sulfate in the resolution of vaginal bleeding and contractions in nonsevere placental abruption.Study Design Thirty women between 24 and 34 weeks of gestation diagnosed with nonsevere placental abruption were randomized to receive magnesium sulfate tocolysis or normal saline infusion. The primary outcome was the proportion of women undelivered at 48 hours with resolution of vaginal bleeding and uterine contractions. Maternal and neonatal outcomes were also compared.Results Fifteen (50%) women received magnesium sulfate tocolysis and 15 (50%) received intravenous saline. There was no difference in the number of women who were undelivered at 48 hours with resolution of vaginal bleeding and contractions in the magnesium sulfate (80.0%) and saline (66.7%; p-value = 0.68) groups. There were no differences between groups in the gestational age at randomization, time to uterine quiescence, time on study drug, length of hospitalization, days from randomization to delivery, incidence of side effects, or admissions to the neonatal intensive care unit.Conclusions Magnesium sulfate tocolysis did not provide a significant difference in pregnancy prolongation in the management of preterm nonsevere placental abruption. Recruitment goals were not met due to the introduction of the use of magnesium sulfate for neuroprotection.
Keywords: magnesium sulfate; placental abruption; third-trimester vaginal bleeding; tocolytics